Tumour Microenvironment-Immune Cell Interactions Influencing Breast Cancer Heterogeneity and Disease Progression - Tan, Keely; Naylor, Matthew J. (Frontiers in Oncology, 2022)
Breast cancer is a complex, dynamic disease that acquires heterogeneity through various mechanisms, allowing cancer cells to proliferate, survive and metastasise. Heterogeneity is introduced early, through the accumulation of germline and somatic mutations which initiate cancer formation. Following initiation, heterogeneity is driven by the complex interaction between intrinsic cellular factors and the extrinsic tumour microenvironment (TME). The TME consists of tumour cells and the subsequently recruited immune cells, endothelial cells, fibroblasts, adipocytes and non-cellular components of the extracellular matrix. Current research demonstrates that stromal-immune cell interactions mediated by various TME components release environmental cues, in mechanical and chemical forms, to communicate with surrounding and distant cells. These interactions are critical in facilitating the metastatic process at both the primary and secondary site, as well as introducing greater intratumoral heterogeneity and disease complexity by exerting selective pressures on cancer cells. This can result in the adaptation of cells and a feedback loop to the cancer genome, which can promote therapeutic resistance. Thus, targeting of the TME and immune-stromal cell interactions has been suggested as a potential therapeutic avenue given that aspects of this process are somewhat conserved between breast cancer subtypes. This mini review will discuss emerging ideas on how the interaction of various aspects of the TME with breast cancer cells contributes to increased heterogeneity and disease progression, and the therapeutic potential of targeting the TME.